2017
DOI: 10.1111/ina.12414
|View full text |Cite
|
Sign up to set email alerts
|

Size and mineral composition of airborne particles generated by an ultrasonic humidifier

Abstract: This study describes the size distribution and concentration of particles expelled by a portable, 3-L ultrasonic humidifier. The ultrasonic humidifier was filled with waters of varying mineral content and hardness. Aerosol size distributions were measured during 8 hours of humidifier operation in a typical bedroom. Humidifiers produced approximately 1.22 × 10 10 -2.50 × 10 10 airborne particles per milliliter of water consumed, resulting in airborne particle concentrations of 3.01-5.91 × 10 4 #/cm 3 , with mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 27 publications
5
34
0
Order By: Relevance
“…Our results show that both the number and size of dried particles increase with increasing solute concentrations in water. This trend is consistent with observations made by Sain et al 13 The unimodal size distribution obtained here is in agreement with a few previous studies which showed that a major fraction of dried particles from an ultrasonic humidifier is in the submicrometer range. 13,30,36,38,39 However, there may be larger particles that are beyond the detection range in the current method, as shown by recent work by Yao et al 38,39…”
Section: Airbeam-smps Intercomparisonsupporting
confidence: 94%
See 2 more Smart Citations
“…Our results show that both the number and size of dried particles increase with increasing solute concentrations in water. This trend is consistent with observations made by Sain et al 13 The unimodal size distribution obtained here is in agreement with a few previous studies which showed that a major fraction of dried particles from an ultrasonic humidifier is in the submicrometer range. 13,30,36,38,39 However, there may be larger particles that are beyond the detection range in the current method, as shown by recent work by Yao et al 38,39…”
Section: Airbeam-smps Intercomparisonsupporting
confidence: 94%
“…11 However, estimates based on sales data and more recent reports suggest that the ultrasonic type occupies the major market share in the US now. 12,13 While the benefits of household humidifiers are widely perceived, potential risks using the ultrasonic humidifier have also been suggested, which are associated with fine particulate matter generated from the humidifier operation. Particulate matter (PM), specifically those with diameters equal to or smaller than 2.5 µm (PM 2.5 ), can penetrate deep into the human respiratory tract and cause a variety of adverse health effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Humidity may play a role in sensory perception of indoor environmental quality 18 . Humidifiers are used to deliberately increase the water vapor content of indoor air; these have the potential to elevate pollutant exposures and health risks 19,20 . In warm and humid climates, much of the energy for air conditioning is used to dehumidify ventilation air 21 …”
Section: Indoor Watermentioning
confidence: 99%
“…PM 10 of 118 and 966 μg/m 3 were emitted in a closed dormitory room of 33.5 m 3 and air exchange rate of 0.87 hr −1 when using 75 and 510 mg/L TDS tap water to fill the humidifiers of water consumption rate at 0.21 L/h, respectively ( Sain and Dietrich, 2015 ). Soluble minerals and insoluble metal oxide particles, when present in fill water in the humidifiers, are emitted as sub-micron, inhalable particulates ( Sain et al., 2018 ; Yao et al., 2019 ). Particles <1 μm can penetrate deeper into the lower lung region and cause mild to severe inflammatory responses depending on the chemical composition.…”
Section: Introductionmentioning
confidence: 99%